Sinusoidal hemangioma with secondary intravascular papillary endothelial hyperplasia - Radhika Yajaman Gurumurthy; Nadig Siddharth Shankar; C S Mohan Raj; Nadig Sriram (Wolters Kluwer Medknow Publications, 2020)
In this case report, we present a case of a 47-year-old man with sinusoidal hemangioma with secondary intravascular papillary endothelial hyperplasia arising in the subcutaneous tissue. To the best of our knowledge, there are only two cases of sinusoidal hemangioma with secondary intravascular papillary endothelial hyperplasia reported till date, both of which were intramuscular hemangiomas. These are rare entities that also have overlapping histomorphological features with that of various other vascular tumors making histopathological diagnosis troublesome at times. Careful histopathological examination aided by immunohistochemical studies in difficult cases is essential to avoid these diagnostic pitfalls.